Identification of gamma-hydroxybutyrate in biological fluids by liquid chromatography with tandem mass spectrometry - Djordjević, Snežana; Brajković, Gordana; Antunović, Marko; Vučinić, Slavica; Kilibarda, Vesna (Archives of Pharmacy, 2022)
Gamma-hydroxybutyrate (GHB) is a substance that belongs to depressors of the central nervous system, and its mechanism of action involves GABA receptors binding. In recent years, there has been an increase in GHB abuse. The maximum GHB blood concentration is reached 20-40 min after oral ingestion, elimination half-life being 30-50 min. About 1-5% of GHB is excreted unchanged in urine, detected only 3-10 h after ingestion. GHB abuse risk is a small difference between dose that causes euphoria and reduced inhibition and the dose that can lead to loss of consciousness cardiorespiratory depression. GHB blood and urine identification is important in poisoning with unknown ethiology diagnosis. This work aimed to present method of liquid chromatography with tandem mass spectrometry (UPLC-MS-MS) GHB detection in biological fluids. There were 21 cases of GHB abuse recorded at the Poison Control Centre, in 2018-2020 period. Immunoassays for the detection of GHB in urine still stayed unavailable for routine laboratory practice, so we developed UPLC-MS-MS method for its detection in urine and serum. Samples were prepared by solid-phase extraction on Oasis HLB cartridges. GHB separation from matrix compounds was performed on a C18 column by mixture of acetonitrile and 5 mmol/L formate buffer pH 3.5 as mobile phase. GHB identification was performed on the basis of the characteristic mass ion m/z 105, 87 and 45. Since GHB overdose can often lead to coma and even death, analytical GHB confirmation in biological fluids has great importance because facilitates poisoning diagnosis and speed up patients treatment.